2012
DOI: 10.1590/s1413-81232012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary, Circulating, and Tissue Biomonitoring Studies Indicate Widespread Exposure to Bisphenol A

Abstract: Estudos de biomonitoração do sistema urinário, circulatório e tecidos indicam grande exposição ao Bisfenol A Resumo Bisfenol A (BPA) é um dos produtos quí-micos mais produzido em todo o mundo, e a exposição humana a ele é considerada onipresente. Assim, há preocupações de que a quantidade de BPA para o qual os seres humanos estão expostos podem causar efeitos adversos à saúde. Nós examinamos muitas possibilidades sobre o porquê estudos de biomonitorização e toxicocinética podem chegar a conclusões aparentement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
331
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(359 citation statements)
references
References 125 publications
19
331
2
6
Order By: Relevance
“…According to physiologically based pharmacokinetic studies, BPA is found in human serum, urine, milk and fat, with plasma levels ranging from 0.2 to 20 ng/mL (or 1 to 100 nM) [1], [2], [3], [4], [5], [6]. This substance is mainly absorbed by the digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…According to physiologically based pharmacokinetic studies, BPA is found in human serum, urine, milk and fat, with plasma levels ranging from 0.2 to 20 ng/mL (or 1 to 100 nM) [1], [2], [3], [4], [5], [6]. This substance is mainly absorbed by the digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…BPA has also been demonstrated to bind to the membrane-bound G-protein coupled ER 1 (GPER, also GRP30) (Bouskine et al, 2009; Sheng and Zhu, 2011), as well as the nuclear receptor estrogen-related receptor (ERR)-γ (Matsushima et al, 2007). BPA levels in human samples including urine, serum, blood, and saliva can vary depending on sample type, study population, and detection method, though reports repeatedly indicated that levels of BPA in humans are in the nanomolar range (Vandenberg et al, 2007, 2012). For example, typical total BPA levels in adult serum and urine range from ~1–90 nM and ~5–10 nM, respectively (Vandenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Unconjugated BPA in blood and conjugated BPA in urine samples have been found in biomonitoring throughout the world 4. Despite the number of studies demonstrating human and environmental exposures and identifying hazards in animal and cellular models, there is still uncertainty as to the major sources and significance of exposure, pharmacokinetics of exposure, and to what extent the effects in animal models are transferable to humans 5.…”
Section: Bpa—science Controversiesmentioning
confidence: 99%